Efficacy of 11C-2β-carbomethoxy-3β-(4-fluorophenyl) tropane positron emission tomography combined with 18F-fluorodeoxyglucose positron emission tomography in the diagnosis of early Parkinson disease: A protocol for systematic review and meta analysis. Issue 51 (18th December 2020) - Jiang, Lei; Wang, Xixian; Li, Pengtao; Feng, Zhaohai; Shi, Xin; Shao, Hua
Abstract: Background: Parkinson's disease (PD) has a high incidence in the elderly, and the late stage seriously affects the daily life of the patients. Most of the initial symptoms of PD are not obvious or atypical, which brings difficulties to the early diagnosis. Replacement therapy and neuroprotection after early diagnosis can significantly improve the prognosis and quality of life of patients. More and more evidence shows that 11 C-2β-carbomethoxy-3β-(4-fluorophenyl) tropane positron emission tomography ( 11 C-CFT PET) combined with 18 F-fluorodeoxyglucose positron emission tomography ( 18 F-FDG PET) can effectively improve the accuracy of early diagnosis. However, there is no consistent conclusion at present. The purpose of this study is to evaluate the efficacy of 11 C-CFT PET combined with 18 F-FDG PET in the diagnosis of early PD. Methods: We will search 7 electronic databases (PubMed, EMBASE, Web of Science, Cochrane library, PsycINFO, AMED, Scopus), ongoing trials and grey literature to collect related randomized controlled trials and will use Review Manager Software 5.2 and STATA Software 16.0 for analysis and synthesis. Results: We will integrate the existing randomized controlled trials to evaluate the value of 11 C-CFT PET combined with 18 F-FDG PET in the diagnosis of early PD. Conclusion: Our study may prove that 11 C-CFT PET combined with 18 F-FDG PET can effectively diagnose early PD. Registration number: International Prospective Register of Systematic Reviews (PROSPERO): CRD42020203442.